Preexercise cycling protocol alters pacing behavior in competitive time trials - Konings, M. J.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The behavior of an opponent has been shown to alter pacing and performance. To advance our understanding of the impact of perceptual stimuli such as an opponent on pacing and performance, this study examined the effect of a preexercise cycling protocol on exercise regulation with and without an opponent. Methods: Twelve trained cyclists performed 4 experimental, self-paced 4-km time-trial conditions on an advanced cycle ergometer in a randomized, counterbalanced order. Participants started the time trial in rested state (RS) or performed a 10-min cycling protocol at 67% peak power output (CP) before the time trial. During the time trials, participants had to ride alone (NO) or against a virtual opponent (OP). The experimental conditions were (1) RS-NO, (2) RS-OP, (3) CP-NO, and (4) CP-OP. Repeated-measures analyses of variance (P < .05) were used to examine differences in pacing and performance in terms of power output. Results: A faster pace was adopted in the first kilometer during RS-OP (318 [72] W) compared with RS-NO (291 [81] W; P = .03), leading to an improved finishing time during RS-OP compared with RS-NO (P = .046). No differences in either pacing or performance were found between CP-NO and CP-OP. Conclusions: The evoked response by the opponent to adopt a faster initial pace in the 4-km time trial disappeared when cyclists had to perform a preceding cycling protocol. The outcomes of this study highlight that perceived exertion alters the responsiveness to perceptual stimuli of cyclists during competition.